The CLAEM and the Argentine Musical Modernity. (Revista Argentina de Musicología, 2018)
Until the emergence of the Latin American Centre for Advanced Musical Studies (CLAEM at the Di Tella Institute), Argentine musical scene could be explained around two almost mutually exclusive tendencies; on the one hand, the musical nationalism with A. Ginastera as its most conspicuous exponent, and on the other, the internationalist one led by J. C. Paz. Both related to a greater or lesser extent with their European counterparts and established models: Ginastera nationalism through Argentine folklore (until at least the fifties) and Paz paradigmatically with Viennese 12-tone music in the thirties and later with the generalization of the serial principle. In this context, the CLAEM produced the dissolution of the historical antinomy and established a so far unknown aesthetic multiplicity. In this work we propose that the generation directly formed in, or directly related to, the Centre carried out the most important aesthetic transformation of Argentine contemporary academic music from the second half of the 20th Century. Our goal is to describe the nature of this transformation and exemplify it analytically in three pieces by representative composers: ...piagne e sospira (1969), by G. Gandini (1936-2013), Música ritual (1971-1974), by M. Etkin (1943) and Ricercare’s blues (1976), by L. Arias (1940).
Keywords: CLAEM; Argentine musical modernity; Gandini; Etkin; Arias